PERAN KANTOR URUSAN AGAMA (KUA) DALAM MENGURANGI PERKAWINAN SIRI - Habibi, Habibi; Musorif, Musorif (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2022)
Unregistered marriages are called underhanded marriages, which are marriages carried out by Indonesian Muslims who have fulfilled the requirements and pillars of marriage according to religion but are not registered with the marriage registrar. The existence of economic factors, remote locations, and complicated administrative requirements make people reluctant to register their marriages. Based on this background, this study aims to determine the role of the Office of Religious Affairs in reducing unregistered or unregistered marriages, while the method used is a qualitative-descriptive approach supported by complete primary and secondary data. The results obtained from research in the community around the Office of Religious Affairs, Kec. Tirtayasa as the primary data source, it is known that the people of Kec. Tirtayasa is not aware of the importance of registered marriages and lacks knowledge of the importance of marriage certificates. So the need for the role of the Office of Religious Affairs in taking action by means of socialization assisted by extension workers and directing directly to the people who want to hold marriages around the district. Tirtayasa.